Efek Suplementasi Vitamin A, Minyak Fortifikasi dan Edukasi Gizi Ibu Nifas terhadap Morbiditas Ibu dan Bayi - Salam, Abdul; Briawan, Dodik; Martianto, Drajat; Thaha, Abdul Razak; Arundhana, Andi Imam (Media Kesehatan Masyarakat Indonesia, 2018)
Vitamin A deficiency can affect the morbidity of postpartum mother and their infant. The purpose of this study was to determine the effect of high doses of vitamin A (2vitA and 1vitA), fortified oil (Forti A) and nutrition education (Education) on maternal and infant morbidity. This study was used quasi experimental design with total 295 samples selected based on the inclusion criteria. Morbidity which mainly associated with ARI and diarrhea was measured every two weeks until the infant is 3 months old. The results showed that the average postpartum mothers in this study were 27 years old and about 42% of postpartum mothers had completed their education up to high school level. The average frequency of maternal ARI in the Forti A group was lower compared to the 2vitA, 1vitA and educational groups (0.04, 0.31, 0.95, and 0.29, respectively) (p<0.000). Likewise, it is also found in the duration of respiratory infection for each group of; 0.17, 0.99, 3.16, and 1.07 day, respectively (p<0.000). Oil fortification with vitamin A can reduce the incidence of morbidity.